Travel decision making during and after the COVID-2019 pandemic: Revisiting travel constraints, gender role, and behavioral intentions - Aziz, Norzalita Abd; Long, Fei; Bhuiyan, Miraj Ahmed; Rahman, Muhammad Khalilur (Frontiers in Psychology, 2022)
The COVID-19 pandemic has deeply influenced the tourism and hospitality industry, and it has also reshaped people’s travel preferences and related behaviors. As a result, how prospective travelers perceive travel constraints and their effects on future travel behaviors may have changed to some extent. Besides, such perception arguably varies across gender. Therefore, this research examines the interplay between travel constraints, gender and travel intentions for facilitating robust tourism recovery by revisiting the Leisure Constraints Model (LCM) from a gender perspective. Data was collected through a survey from 357 Malaysian prospective travelers. By conducting path analysis and multigroup analysis (MGA), it is found that structural and interpersonal constraints impose indirect effects on travel intentions (mediated by intrapersonal constraints), and gender moderating the effect of structural cost on intrapersonal constraints and effect of intrapersonal constraints on travel intentions. Based on these findings, this research provides theoretical and practical implications into how to adjust their marketing strategies and travel products during the era of “new normal” for tourism policy makers, destination marketers and related businesses.